Impressive Female Figures in Three Selected Plays of Caryl Churchill - Ravari, Zahra Khozaei; Naidu, Sivabala (Richtmann Publishing, 2011)
This study aims to show how Caryl Churchill, a woman feminist playwright has played a significant role in contemporary literary studies. Churchill’s plays mostly illustrate the oppression of women in patriarchal societies. By illustrating these subjugated and oppressed female characters, Churchill strikes the attention of the audience and make them to criticize the established social and economical norms. The blatant abuse of women in male dominated societies had resulted in a continuous struggle by them throughout history who fought for equal opportunities as they attempted to improve their positions in the society they lived in. In this regard, in researcher’s opinion Churchill also illustrates some subverssive characters among these oppresed women that although cannot change the present situation, they defy the conventional norms and challenge for their rights. This study places its crucial lens on portraying these impressive female characters in Churchill’s selected plays, Vinegar Tom (1976), Cloud Nine (1979), and Top Girls (1982). It also aims to focus on social construction of gender in the characters of these selected plays. Keywords: Feminist Plays, Agency, Subjectivity, Social Construction of Gender, Drag, Performativity.